The Twilight of the Scientific Age by Martín López Corredoira - Bauer, Henry (Journal of Scientific Exploration, 2014)
<!–[if gte mso 9]> <![endif]–> Was man made for science or science made for man?”, quoted more than once, constitutes the central theme in this book. Corredoira’s answer is that science may once have been to the benefit of humanity but that it no longer is: too many outside vested interests, too much “scientific” activity coopted and driven by interests other than truth-seeking (commercial and official powers), in the larger context of an overall intellectual mediocrity of contemporary society including all too many scientists. Many pundits would readily agree with these and related points. Unfortunately, the book does little to add supporting value to its assertions. It’s an expanded version of an essay of the same title (Corredoira 2103) and doesn’t work so well in book form. Perhaps the essay works better than the book because essays are quite properly subjective pieces whereas books (other than autobiographies or memoirs, of course) are expected to deal more objectively with their topic. The book is full of forcefully expressed but unsupported opinions, including rants against capitalism, the power of money, and the ugliness that comes with “progress”. For instance, Corredoira regrets the homogenization of national cultures because “The character of people is not the same everywhere” (p. 167) (which is doubtfully relevant to the question of whether the scientific age is in its twilight). Corredoira approves the view that it would be a pity for “India, for instance” to produce “western-style science” — but Sir C. V. Rahman, Jayant Narlikar, and other eminent Indian scientists could justifiably disagree; “it is as shocking that some countries try to produce science as it would be to see a Japanese man playing flamenco music” (p. 169) — yet Japanese and Indians among other Asians have excelled at classical Western music. As for twilight, “Since the goal of science as an institution is mostly socioeconomic — keeping a structure which creates employment for myriad members of the guild, and allowing some people to acquire some power — the evolution of scientific knowledge will not directly affect its existence. The problem for scientific institutions will come when its influence over society is reduced and when the resources that science consumes begin to diminish” (p. 143). <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif"; –> <!–[endif] –>